2011
DOI: 10.1002/pts.972
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Sealing of Flexible Packaging Films – Principle and Characteristics of an Alternative Sealing Method

Abstract: The closure process for packaging is a key process. It ensures the protective function of packaging and assures the packaged goods a long life. In this context, efficient and reliable sealing processes are essential for the production of sustainable packages.In this paper, several characteristics of the ultrasonic sealing process will be discussed and accompanied by experimental results. The introduction provides an insight into the ultrasonic sealing process, its heating mechanisms and the process steps. A co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 12 publications
(17 reference statements)
2
36
0
Order By: Relevance
“…The results showed that the elderly and the young groups exhibited significantly different torque and force profiles when attempting to open the bottles. Similar work was also conducted by researchers focusing on the opening force measurement and opening postures of bottles and jars [17][18][19][20][21][22][23][24][25][26].This interest in understanding the issues around openability has led to the development of European and international guidelines on the measurement of packaging seal forces and user test panel methods. The European technical specification DD CEN/TS 15945 [26] launched in 2011 sets out a framework for ease of opening evaluation for packaging and has more recently been superseded by ISO17480.…”
Section: Introductionmentioning
confidence: 85%
“…The results showed that the elderly and the young groups exhibited significantly different torque and force profiles when attempting to open the bottles. Similar work was also conducted by researchers focusing on the opening force measurement and opening postures of bottles and jars [17][18][19][20][21][22][23][24][25][26].This interest in understanding the issues around openability has led to the development of European and international guidelines on the measurement of packaging seal forces and user test panel methods. The European technical specification DD CEN/TS 15945 [26] launched in 2011 sets out a framework for ease of opening evaluation for packaging and has more recently been superseded by ISO17480.…”
Section: Introductionmentioning
confidence: 85%
“…In scientific and technical papers, several tests are performed on packaging films with contaminated seals such as seal strength, leak rate, and degree of particle encapsulation (caulkability) . This study is focussed on seal strength.…”
Section: Introductionmentioning
confidence: 99%
“…The relation of seal through contamination and hot tack performance is part of this study. In the last decades, the influence of seal material composition on the contaminated seal performance was the topic of a limited amount of studies, and these studies did not include a well‐described application method for solid contamination . Moreover, there are no methods described in these studies to obtain the optimal or maximal seal performance through contamination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several advantages of ultrasonic sealing over heat conductive sealing have been shown, such as the short sealing times, decreased thermal stress on the packaged product, the capability to seal through powder contamination, a decreased energy consumption, a narrower seal, and no need for thick peel layers. 2,[7][8][9] In ultrasonic sealing, sound waves in the frequency range between 20 and 40 kHz are used to create friction and thus generate heat between two layers of packaging film. The energy introduction in the seal is achieved by means of an ultrasonic horn, oscillating with an amplitude in the range of 10-60 μm, and an anvil.…”
Section: Introductionmentioning
confidence: 99%